Hak dan Kewajiban Dalam Jaminan Hipotik: Kajian Dalam Asas Proporsionalitas Dalam Perjanjian Kredit - Rahmania, Dian; Hermawan, Arik; M, Maghfiroh; M, Mu’ariah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Credit agreements that use mortgage collateral play an important role in the Indonesian economic system, especially in providing legal certainty for creditors. However, the application of rights and obligations in credit agreements involving mortgage collateral is often unbalanced between debtors and creditors, which can lead to injustice. This paper explores the rights and duties of debtors and creditors in mortgage-backed credit agreements, with a focus on the proportionality principle. Using a normative qualitative approach through legal analysis and case studies, it reveals that while mortgages grant creditors strong enforcement power upon default, debtors’ rights are frequently overlooked, especially in disproportionate execution. The proportionality principle within credit contracts is designed to maintain equilibrium between a borrower’s duties and a lender’s entitlements; however, its real-world application frequently falls short. This paper advocates for a legal overhaul that intensifies the focus on safeguarding borrower rights and enforces a more rigorous application of proportionality to establish just and equitable credit arrangements.